Pedestrian Comfort Analysis and Parameterized Optimization Design for Raised Floors - Juanli Guo; Haonan Liang; Jiehui Wang; Yijie Cao (Applied Sciences, 2025)
Pedestrian comfort is not only related to the health of the human body, but also directly impacts the efficiency and lifespan of building materials. Raised floors have more complex geometric characteristics and structural dynamic properties compared to traditional flooring, which necessitates an analysis of pedestrian comfort. This study explores four different configurations of raised floors in prefab bathroom units to evaluate their pedestrian comfort. Through theoretical and experimental modal analysis, the natural frequencies and potential deformation areas are identified, enabling the calculation of peak acceleration of the raised floors under walking excitation. The study then quantitatively assesses the pedestrian comfort of raised floors based on natural frequency and peak acceleration measurements, proposing an optimization design method using a multi-island genetic algorithm (MIGA). By adjusting parameters such as the support leg distance, beam shape, and support board surface layer thickness, an optimal balance between pedestrian comfort and heat transfer performance is achieved. Through the integration of simulation and experimental techniques, the study presents an efficient and cost-effective optimization design method for raised floors and explores the impact mechanism between design variables and pedestrian comfort performance.